The Impact of Budget Efficiency Policies on Competition in Government Construction Tenders: Evidence from East Kalimantan Province - Johantri, Bagas; Budi Nata Gama (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to examine the impact of government budget efficiency measures on competition in public procurement, specifically construction tenders for small enterprises in East Kalimantan Province. It seeks to understand whether efficiency-driven budget cuts influence the number of participants. A quantitative approach was employed using secondary data from the national procurement platform. A total of 335 tenders before efficiency and 124 tenders after efficiency were analyzed using descriptive statistics and the nonparametric Mann–Whitney U Test. The analysis shows a significant increase in the median number of participants per tender after the efficiency policy. This study provides empirical evidence on how fiscal efficiency policies reshape procurement competition at the regional level. The research highlights how budget efficiency policies shape SME competition in government tenders and examines the potential effects of this intensified competition for both the government and SMEs. Government efficiency policies may enhance price competitiveness but risk marginalizing small enterprises. Regulatory adjustments and tender restructuring are recommended to ensure inclusive participation.